Recurrent Posterior Reversible Encephalopathy Syndrome in an Adolescent Boy with End-Stage Renal Disease - Andrew Shieh; Natalie Darro (Hindawi Limited, 2021)
Posterior reversible encephalopathy syndrome (PRES), also known as reversible posterior leukoencephalopathy syndrome, is a neurological entity characterized by acute change in consciousness, visual impairment, headache, and seizures. It is associated with autoimmune disease, immunosuppressive agents, organ transplantation, acute glomerulonephritis, and sepsis. Typically, vasogenic edema is seen in the white matter of parieto-occipital lobes but can also involve atypical locations such as frontal lobes, thalamus, basal ganglia, and gray matter. While occurring extensively in adults, few cases, especially recurrent episodes, have been described in children. We report a case of recurrent PRES in a 17-year-old boy with end-stage renal disease on a peritoneal dialysis program who initially presented with hypertension and seizures. He emergently received intravenous antihypertensive medication with immediate and sustained improvement in his mental status. Information about recurrent PRES in children is limited because it is not commonly seen. We examine the clinical features of PRES and highlight important points for the diagnosis and management of this rare syndrome. This report demonstrates the importance of pediatricians to consider PRES in the differential diagnosis in children presenting with acute altered mental status. Blood pressure measurements, which are often overlooked in pediatric care, may assist in correctly diagnosing patients.